Multidrug-Resistant Bacteria Colonization in Patients Admitted to Dr. Cipto Mangunkusumo Hospital Jakarta, Indonesia - Selvi Nafisa Shahab; Anis Karuniawati; Omar Mukhtar Syarif; Yulia Rosa Saharman; Robert Sinto; Pratiwi Pujilestari Sudarmono (Interna Publishing, 2024)
Background: Antibiotic resistance is the main problem in infectious disease management. Multidrug-resistant (MDR) bacteria could be carried by admitted patients and become a source of spread in the hospital, causing infections in other patients or the patients themselves. However, the screening of MDR bacteria has not been a standard in developing countries. This study aimed to get the prevalence of MDR bacteria colonization in patients on admission to Dr. Cipto Mangunkusumo Hospital. Methods: Selective liquid media with added antibiotics were used for culturing the MDR bacteria. While admitted to the hospital, subjects were sampled and interviewed to fill out a questionnaire. The screening specimens used for this study were throat, navel, rectal, nasal, and armpit swabs. During hospitalization, hospital-acquired infections (HAIs) were recorded. Results: Of 100 patients included in the study, the prevalence of MDR bacteria colonization on admission was 63% (n=63) with the prevalence of CR-GNB, ESBL-PE, and MRSA were 11%, 54%, and 11%, respectively. Two-thirds of the patients with HAIs (n=8/12) were colonized with MDR bacteria. Factors associated with MDR bacteria colonization were the recent use of invasive medical devices and comorbidity, while a factor associated with CR-GNB colonization was the recent use of antibiotics. Conclusion: The prevalence of MDR bacteria colonization in patients on admission to Dr. Cipto Mangunkusumo Hospital in 2022 was 63% (n=63), of which 12.68% (n=8) experienced HAIs during hospitalization. MDR bacteria colonization was associated with the recent use of invasive medical devices and comorbidity. History of antibiotic use was associated with CR-GNB colonization.